Enhancing the recovery of oilseed rape seed oil bodies (oleosomes) using bicarbonate-based soaking and grinding media - De Chirico, Simone; Di Bari, Vicenzo; Foster, Tim; Gray, David A. (Elsevier, 2018)
An aqueous process for the recovery of oil bodies from rapeseed using sodium bicarbonate-based soaking and grinding media (pH 9.5) was investigated. The effect of the ratio between seed and mass of media during grinding and molarity of the medium used on oil body integrity, purity and storage stability have been studied. The grinding of seeds in solution at a ratio of 1:7 (w/w) significantly improved the quality of oil body suspension to a size more in-line with that seen in vivo (average D4,3 of 1.19 μm). The purity and the composition of the recovered oil bodies depends on the molarity of medium used; the use of a sodium bicarbonate solution (pH 9.5, 0.1 M) in the grinding and washing steps produced oil body preparations with the same purity as that resulting from washing a crude preparation with 9 M urea. The resultant emulsion had improved physical stability over a storage period of one month.